Bacterial profile and antimicrobial susceptibility pattern of anterior blepharitis in Misurata region, Libya - Abdalla Alsidig Musa; R Nazeerullah; Salem R Sarite (Wolters Kluwer Medknow Publications, 2014)
A total of 56 anterior blepharitis cases including 22 cases of ulcerative blepharitis and 34 cases of seborrheic blepharitis were studied. The predominant age group of anterior blepharitis cases was above 40 years. With males affected more than females. In the order of decreasing frequency, the isolated bacteria from anterior blepharitis in order of decreasing frequency were Staphylococcus aureus 14 (25%), Staphylococcus epidermidis 14 (25%), similar Klebsiella species 10 (18%), viridans Streptococci five (9%), Pseudomonas aeruginosa five (9%), Proteus species four (7%), Enterobacter aerugenes three (5%), and Escherichia coli one (2%). The common isolates observed in both samples were S. aureus, S. epidermidis, and Proteus species. The Gram-positive cocci S. aureus were resistant to four antibiotics and viridans Streptococci were resistant to three antibiotics, whereas the Gram-negative bacteria were resistant to two antibiotics. Improper selection of antibiotics, inadequate dosing, and poor compliance to therapy may play an important role in increasing resistance. Identification of anterior blepharitis pathogens and performing antibiotic susceptibility test are important factors in reducing the resistance to therapy.